Penerapan Teori Belajar dalam Menanamkan Nilai Agama dan Moral pada Anak Usia 5-6 Tahun - I Nyoman Suarta; Ika Rachmayani; Muazzar Habibi; Baiq Khofifah Kusuma Putri (Indonesian Publication Center, 2021)
Every teacher has a way of instilling religious and moral values in early childhood. But how to instill religious and moral values varies according to the type of teacher's qualifications. The purpose of this study is to find out the theory of learning in instilling religious and moral values in children aged 5-6 years applied by teachers based on teacher qualifications in Praya District of Central Lombok in 2021. The research method used is quantitative with this type of survey research. Data analysis uses percentages. The results showed that pgpaud S1 certified teachers chose behavioristic learning theory at 66.66%, cognitivistic at 100% worship practice, 50% welcome, 50% storytelling, and constructivistic singing at 83.33%, playing 83.33% role. Teachers certified non-S1 PGPAUD chooses cognitivistic learning theory on eating 100%, worship practices 83.33%, singing 100%, welcoming 83.33%, telling 66.66%, playing a role 83.33%. Pgpaud's non-certification master chose behavioristic learning theory at 66.66%, singing 33.33%, cognitivistic on worship practice 100%, singing 33.33%, welcoming 66.66%, telling 83.33%, playing 50% role, and constructivistic singing 33.33%, playing 50%. Non-certification non-S1 PGPAUD teachers chose behavioristic learning theory at eating 66.66%, singing 33.33%, welcoming 50%, telling 50%, cognitivistic at worship practice 100%, singing 33.33%, welcoming 50%, playing a 50% role, and constructivistic on singing 33.33%, playing a role of 50%. So, group B teachers in Praya Subdistrict on average use behavioristic learning theory on the method of implementing eating activities. Kognitivistic learning theory on methods of applying the practice of worship, singing, welcoming, telling, role-playing. Constructivistic theory on methods of application of role-playing.